1984
DOI: 10.1007/bf02537405
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of lipid metabolism and membrane physical state by an actively and passively overwintering planktonic crustacean

Abstract: Phospholipid (PL) composition, fatty acid (FA) composition of total and major individual PL as well as the physical state of isolated PL were investigated in relation to temperature exposure by freshwater planktonic crustaceans,Cyclops vicinus andDaphnia magna. C. vicinus, adapted to warm water, accumulated appreciable amounts of docosahexaenoic acid in its PL within 3 days when the temperature was decreased from 20 C to 10 C. Docosahexaenoic acid was preferentially esterified to phosphatidylethanolamine (PE).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…In addition, Schlechtriem et al (2006) found that retention of EPA by daphnids was clearly influenced by temperature because significantly higher levels of EPA were found in individuals reared at 11uC compared with those kept at 22uC, suggesting that EPA requirements of cladocerans increase with decreasing temperature. Farkas (1984) argued that the ability of zooplanktonic species to adapt their membranes at low temperature depends on their ability to incorporate PUFA. More generally, the level of unsaturation of fatty acids of poikilotherms increases at low temperature in membrane lipids, lending support to Schlechtriem's and Farkas's results (Nishida and Murata 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Schlechtriem et al (2006) found that retention of EPA by daphnids was clearly influenced by temperature because significantly higher levels of EPA were found in individuals reared at 11uC compared with those kept at 22uC, suggesting that EPA requirements of cladocerans increase with decreasing temperature. Farkas (1984) argued that the ability of zooplanktonic species to adapt their membranes at low temperature depends on their ability to incorporate PUFA. More generally, the level of unsaturation of fatty acids of poikilotherms increases at low temperature in membrane lipids, lending support to Schlechtriem's and Farkas's results (Nishida and Murata 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In nature, cladocerans have thus to optimize their fitness with a trade-off between temperature and food availability. Earlier work from Farkas et al (1984) investigated the effect of temperature on zooplankton's ability to adapt their cell membrane lipid composition. Unlike the complete fatty acid adaptation in membranes of Cyclops vicinus to changing temperature, Farkas et al (1984) argued that Daphnia magna fails to incorporate PUFA into phospholipids at lower temperatures and suggested that failure to overwinter in an active state is related to their ability to adapt the lipid composition of their cell membranes to lower (winter) temperatures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary deficiency in EPA content has been shown to have greater effect on zooplankton growth and reproduction at lower temperatures (Masclaux et al 2009). PUFAs, such as EPA, are important for maintaining membrane fluidity of ectotherms at low temperatures, and some aquatic ectotherms are capable of increasing the PUFA content of their lipid membranes in response to cold (Farkas et al 1984). However, Daphnia have shown low rates of conversion of C18-PUFA into EPA (Farkas et al 1984;Weers et al 1997), and their fatty acid composition largely resembles that of their diet (Weers et al 1997).…”
mentioning
confidence: 99%
“…PUFAs, such as EPA, are important for maintaining membrane fluidity of ectotherms at low temperatures, and some aquatic ectotherms are capable of increasing the PUFA content of their lipid membranes in response to cold (Farkas et al 1984). However, Daphnia have shown low rates of conversion of C18-PUFA into EPA (Farkas et al 1984;Weers et al 1997), and their fatty acid composition largely resembles that of their diet (Weers et al 1997). Therefore Masclaux et al (2009) suggested that a higher dietary supply of EPA might be required at low temperatures.…”
mentioning
confidence: 99%